1984
DOI: 10.1021/bi00320a013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interchain disulfide crosslinks on the trypsin cleavage pattern and conformation of myosin subfragment 2

Abstract: The ability of 5,5'-dithiobis(2-nitrobenzoate) (Nbs2) to produce interchain disulfide cross-links in both the long and short forms of myosin subfragment 2 (S2) and the conformational effects of these cross-links have been investigated. Short S2 (residues 3-287) contains two pairs of Cys residues at positions 66 and 108, and long S2 (residues 1-440) contains an additional pair at position 410. The reaction kinetics of each form of S2 with Nbs2 was biphasic. During the fast kinetic phase the reaction resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The observation that the pyrene probes at Cys 190, located 2/3 from the amino terminal end, can inhibit polymerizability reinforces the previous result that the binding of pyrene1,-Tm to F-actin is reduced primarily through the weakening of end-to-end interactions (Ishii and Lehrer, 1985). Thus, perturbations can be transmitted over large distances in coiled-coil, rod-like molecules (Edwards and Sykes, 1980;Ueno, 1984;Lu and Lehrer, 1984). It has been postulated that Ca2 -regulation involves troponin perturbation of Tm near Cys 190 (Lehrer et al, 1981), although a model involving direct interaction of troponin at the Tm ends has also been suggested Smillie, 1982, 1983).…”
Section: Discussionsupporting
confidence: 83%
“…The observation that the pyrene probes at Cys 190, located 2/3 from the amino terminal end, can inhibit polymerizability reinforces the previous result that the binding of pyrene1,-Tm to F-actin is reduced primarily through the weakening of end-to-end interactions (Ishii and Lehrer, 1985). Thus, perturbations can be transmitted over large distances in coiled-coil, rod-like molecules (Edwards and Sykes, 1980;Ueno, 1984;Lu and Lehrer, 1984). It has been postulated that Ca2 -regulation involves troponin perturbation of Tm near Cys 190 (Lehrer et al, 1981), although a model involving direct interaction of troponin at the Tm ends has also been suggested Smillie, 1982, 1983).…”
Section: Discussionsupporting
confidence: 83%
“…Lu and Lehrer reported that there are three highly conserved cysteine residues in rabbit skeletal S2 at position a at the 68th, 110th, and 412nd residues, which could also be found in pollack S2 at the same positions. 21 Systematic study with synthetic model peptides revealed that the stability of a double‐stranded coiled‐coil can increase significantly, when cysteine residues are placed in heptad positions d and form a disulfide bond. 20,21 In addition, when the disulfide bond is artificially introduced by 5,5’‐dithio‐bis(2‐nitrobenzoic acid) into the hydrophobic interface between two α‐helices, it considerably increases protein stability without a change in protein structure.…”
Section: Resultsmentioning
confidence: 99%
“… 21 Systematic study with synthetic model peptides revealed that the stability of a double‐stranded coiled‐coil can increase significantly, when cysteine residues are placed in heptad positions d and form a disulfide bond. 20,21 In addition, when the disulfide bond is artificially introduced by 5,5’‐dithio‐bis(2‐nitrobenzoic acid) into the hydrophobic interface between two α‐helices, it considerably increases protein stability without a change in protein structure. 22 However, functional significance of these conserved thiols in S1 heavy chain has remained unsolved.…”
Section: Resultsmentioning
confidence: 99%
“…There are six cysteine residues in myosin rod, three highly conserved in myosin S2 and three in LMM 27 . It is known that there are three highly conserved cysteine residues at position a in myosin rod.…”
Section: Resultsmentioning
confidence: 99%